Identification and Prevalence of Blood Protozoa on Culling Layer Hen Sold in Wonokromo Traditional Market Surabaya City - Moch. Rizky Darmawan; Poedji Hastutiek; Sunaryo Hadi Warsito; Dian Ayu Permatasari; Ririn Ririn; Arimbi Arimbi (Journal of Parasite Science (JoPS), 2022)
The most common types of blood protozoa in chickens are from the phylum of Apicomplexa, including Plasmodium, Leucocytozoon and Haemoproteus. Blood protozoan diseases can cause decreased egg production, stunting and death in poultry farms. This study aims to identify and calculate the prevalence of blood protozoan infection in casted off laying chickens sold at Wonokromo Market, Surabaya City. One hundred blood samples from casted off laying chickens were taken by purposive sampling method. Blood samples were collected in Ethylene Diamine Tetra Acetate (EDTA) tubes, and then taken to the Parasitology Laboratory to make a blood smear which was then examined using a microscope with a magnification of 1000x. The results showed that the single infection was 43% positive for Plasmodium sp., 3% positive for Leucocytozoon sp. and 3% for mixed infections (Plasmodium sp. and Leucocytozoon sp.), with a total prevalence of positive samples infected with blood protozoa was 49%.